Bridge Plate Distraction for Complex Distal Radius Fractures: A Cohort Study and Systematic Review of the Literature - Esworthy, George P.; Shaji, Vibha; Duraku, Liron; Wu, Feiran; Power, Dominic M. (Journal of Wrist Surgery, 2023)
Background Dorsal bridge plating (DP) of the distal radius is used as a definitive method of stabilization in complex fracture configurations and polytrauma patients.Questions/Purposes This review aims to summarize the current understanding of DP and evaluate surgical outcomes.Methods Four databases were searched following the Preferred Reporting Items for Systematic Review and Meta-Analyses guidelines and registered with PROSPERO. Papers presenting outcome or complication data for DP were included. These were reviewed using the National Institutes of Health Quality Assessment and Methodological Index for Non-Randomised Studies tools. Results were collated and compared to a local cohort of DP patients.Results Literature review identified 416 patients with a pooled complication rate of 17% requiring additional intervention. The most prevalent complications were infection/wound healing issues, arthrosis, and hardware failure. Average range of motion was flexion 46.5 degrees, extension 50.7 degrees, ulnar deviation 21.4 degrees, radial deviation 17.3 degrees, pronation 75.8 degrees, and supination 72.9 degrees. On average, DP removal occurred at 3.8 months. Quality assessment showed varied results.There were 19 cases in our local cohort. Ten displayed similar results to the systematic review in terms of range of motion and radiographic parameters. Higher QuickDASH scores and complication rates were noted. Local DP showed earlier plate removal at 2.9 months compared to previous studies.Conclusion DP is a valid and useful technique for treating complex distal radius fractures. It displays a lower risk of infection and pain compared to external fixation which is commonly used to treat similar injuries. Patients can recover well following treatment both in function and range of motion. Further high-quality studies are required to fully evaluate the technique.
Keywords: distal radius; bridge plate; spanning plate; distraction plate; systematic review